VD_FINDINFO HC / 2010 / 656 vom 9. Dezember 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, EFFICACITÉ, RÉSILIATION, SOLIDARITÉ PASSIVE | 257d CO, 273 al. 1 CO, 544 al. 3 CO, 457 CPC, 23 LPEBL